Psychotic temptation - Abensour, Liliane; Alcorn, David (Abingdon [England] ; New York : Routledge, 2013)
"How can we understand the pull towards that which we fear: psychosis? In this thought provoking book, Abensour proposes the idea of a temptation towards psychosis rather than a regression, as a response to the hatred or denial of the subject's origins. She shares her reflections on her psychoanalytic work with psychotic patients focusing on their struggle to achieve a coherent sense of a self that can inhabit a shared world. Abensour locates this struggle within the universal human struggle to achieve a balance between what we can and cannot allow ourselves to know about the reality of death and of our insignificance in the world"--
pt. 1. The time of psychosis : from "actual" to "present" -- pt. 2. A space for psychosis : from writing to psychoanalytic psychodrama -- pt. 3. The vertigo of creation.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Psychoses; Psychoanalysis; Mental illness; Electronic books